2009
DOI: 10.1159/000251960
|View full text |Cite
|
Sign up to set email alerts
|

PHF10 Is Required for Cell Proliferation in Normal and SV40-Immortalized Human Fibroblast Cells

Abstract: Normal human diploid fibroblasts have limited life span in culture and undergo replicative senescence after 50–60 population doublings. On the contrary, cancer cells typically divide indefinitely and are immortal. Expression of SV40 large T and small t antigens in human fibroblasts transiently extends their life span by 20–30 population doublings and facilitates immortalization. We have identified a rearrangement in chromosome 6 shared by SV40-transformed human fibroblasts. Rearrangements involving chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 90 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…As shown previously, PHF10 RNAi resulted in a loss of cell proliferation 19 . Therefore, we studied the effect of PHF10-P and PHF10-S on the proliferation capacity of stably transfected HEK293 cells.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…As shown previously, PHF10 RNAi resulted in a loss of cell proliferation 19 . Therefore, we studied the effect of PHF10-P and PHF10-S on the proliferation capacity of stably transfected HEK293 cells.…”
Section: Resultsmentioning
confidence: 67%
“…Until recently, only one human transcript encoding PHF10 and one encoding a PHF10 variant lacking 2 amino acids in the SAY domain were annotated in NCBI. In addition, 4 mRNAs corresponding to the PHF10 gene were detected in human fibroblasts by northern blot analysis 19 . We determined the structure of PHF10 transcripts in the HEK293 cell line (see Supplementary Material) and revealed 3 novel transcripts among them in addition to that annotated in NCBI (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterozygote genotype of rs318699 was associated with increased expression of PHF10 and increased MD. Banga et al 2009 reported that PHF10 function is required for cell proliferation [50] thus we hypothesise here that PHF10 could possibly contribute to higher MD through increased cell proliferation in the breast.…”
Section: Genes Involved In Signalling May Affect MDmentioning
confidence: 67%
“…PHD Finger Protein 10. Might be neuron specific [56], required for cell proliferation in normal fibroblasts [130]. Tumor suppressor role in uveal melanoma [131].…”
Section: Phf10 (Baf45a) *mentioning
confidence: 99%